Formic acid oxidation reaction on Au(111) electrodes modified with 4-mercaptopyridine SAM. (20th August 2021) - Hermann, Johannes M.; Müller, Heiko; Daccache, Layal; Adler, Christiane; Keller, Sarah; Metzler, Martin; Jacob, Timo; Kibler, Ludwig A.
Graphical abstract: Image, graphical abstract Abstract: The formic acid oxidation reaction (FAOR) on Au(111) electrodes modified by a 4-mercaptopyridine self-assembled monolayer (SAM) was studied with electrochemical techniques and surface-enhanced Raman spectroscopy (SERS). The adsorption of 4, 4'-dithiodipyridine on Au(111) leads to a tremendous enhancement (up to 31-48 times) in electrocatalytic activity for FAOR, which is unique compared to other SAM molecules. The influence of 4, 4'-dithiodipyridine and similar aromatic SAM molecules on Au(111) towards formic acid oxidation was studied systematically as a function of coverage and electrolyte composition. Several parameters such as position and availability of the pyridine nitrogen, adsorption and configuration of the SAM molecules, and the number of free gold sites exert a distinct effect on the formic acid oxidation on SAM-modified Au(111) electrodes and result in different enhancement of electrocatalytic activity. While various coverages of 4-mercaptopyridine enhance the activity towards FAOR on Au(111), the striped ( 5 × 3 ) SAM shows a tremendous activating effect after the addition of HCOOH to HClO4 . In this way, 4-mercaptopyridine efficiently prevents the adsorption of strongly bound, non-reactive formate. The unique enhancement of this specific striped 4-mercaptopyridine adlayer renders FAOR a convenient test reaction to monitor self-assembly processes on Au(111).